Developing critical reading of persuasive materials among high school students - Samia, Natividad Aranas 1928- (1974)
Sample exercises for the development of critical reading skills among first year to fourth year high school students are presented in this study. The writer used 10 representative persuasive materials from local newspapers and magazines from which questions intended to develop critical reading skills were made.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Reading (Secondary education).